2020
DOI: 10.3126/jngmc.v17i2.28749
|View full text |Cite
|
Sign up to set email alerts
|

Serum Creatine Kinase Muscle-Brain Fraction (CK-MB) and Lactate Dehydrogenase (LDH) as Markers of Perinatal Asphyxia in Term Neonates

Abstract: Background: The enzymes CK-MB & LDH are used as potential predictors of timing and grade of HIE in newborns with perinatal asphyxia. Objectives: To differentiate HIE neonates from non-HIE ones on the basis of significant rise of LDH & CK-MB. Methodology: Prospective cross-sectional analytical study. Among 164 newborns, 82 comprising the cases and 82 neonates comprising the controls met the inclusion and exclusion criteria. The umbilical cord blood samples for CK-MB and LDH was drawn and sen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Another condition that worsened the placenta–foetal gas exchange was uterine hypercontractility, which occurred suddenly after a normally evolving labour. The literature is consistent in demonstrating that uterine tachysystole gives no time for placental reperfusion and foetal recovery [ 13 ]. There is a lack of evidence as to whether COVID-19 infections can also affect the uterine muscle and interfere with normal contractility in labour.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Another condition that worsened the placenta–foetal gas exchange was uterine hypercontractility, which occurred suddenly after a normally evolving labour. The literature is consistent in demonstrating that uterine tachysystole gives no time for placental reperfusion and foetal recovery [ 13 ]. There is a lack of evidence as to whether COVID-19 infections can also affect the uterine muscle and interfere with normal contractility in labour.…”
Section: Discussionmentioning
confidence: 88%
“…We used blood lactate dehydrogenase (LDH) [ 11 , 12 ], creatine-kinase (CK) and creatine-kinase muscle-brain (CK-MB) [ 13 ] as markers of tissue hypoxia. LDH was increased during the first 3 days of life, but the values were under the cut-off value for risk of severe prognosis (1054 U/L) [ 12 ].…”
Section: Case Reportmentioning
confidence: 99%
“…Other studies found that CK-MB was not helpful in predicting myocardial injury in a group of infants with neonatal hypoxic ischemia, and levels of CK-MB do not help distinguish between asphyxiated newborns and normal infants. Therefore, CK-MB may not be helpful in identifying infants with neonatal hypoxic ischemia who have cardiovascular compromise but may be more useful as part of a predictive model for poor outcome following neonatal hypoxic ischemia (7,8) .…”
Section: Introductionmentioning
confidence: 99%